RISK FACTORS FOR THE DEVELOPMENT OF STRESS FRACTURES: A CASE CONTROL STUDY - Khan, Aizaz Saleem; Sadiq, Ambreen; Khan, Muhammad Qaiser Alam; Syed, Hassan Mehmood; Mukarrum, Sana (Pakistan Armed Forces Medical Journal, 2020)
Objective: To identify the risk factors for the development of stress fractures in this sub population in our country. Study Design: Comparative cross sectional study. Place and Duration of Study: Combined Military Hospital Abbottabad Pakistan, from Jan 2015 to Aug 2017. Methodology: This study was conducted to identify different variables as risk factors for stress fractures in training cadets. We analyzed age, gender, running and sports prior to joining training, duration of marching, daily milk and carbonated drinks consumption, cigarette smoking, serum albumin, calcium and vitamin D levels, calf muscle diameter, leg length discrepancy and tibiofemoral angles. Results: A total of 275 participant included in this study, 140 cases, 51% and 135 controls, 49%. Mean age was 20 years. Two hundred and sixty eight (97%) were males and 7 (3%) were females. Grade-2 stress fracture was the commonest with 63 (45%) cases. Regular daily running prior to joining training p<0.006, regular milk intake p<0.005 were found to have a protective effect while subnormal serum calcium level p<0.001, serum vitamin D insufficiency p<0.009, thinner calf diameter p<0.001, heavy daily march p<0.039, leg length discrepancy p<0.025 were significant risk factors. Fourteen percent needed operative treatment. Conclusion: Regular daily running prior to joining training, regular milk intake, thicker calf diameter has a protective effect, while subnormal serum calcium and serum vitamin D levels, daily heavy march, leg length discrepancy are significant risk factors.